Transformative Supervision Practices in Enhancing Teacher Work Motivation: Evidence from Rural Primary Education in Indonesia - Efni Yuher Lona; Jamilus Jamilus; Dona Afriyani; Muhammad Fazis; Yusuf Salam (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study examines the implementation of academic supervision in rural Indonesian elementary schools, focusing on how instructional leadership practices are operationalized through planning, organization, execution, and collaborative engagement. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving principals and teachers, and analyzed thematically using the Miles and Huberman framework. The findings reveal that academic supervision is implemented in a systematic, structured, and evidence-based manner that reflects contemporary instructional leadership principles. Planning is grounded in data-driven decision-making based on school evaluation results and teacher performance analysis, particularly in literacy and numeracy development. Organizational practices demonstrate adaptive grouping strategies that enable targeted and context-sensitive supervision. The implementation phase includes administrative verification, classroom observation, feedback delivery, and follow-up actions aligned with planned supervision objectives. In addition, supervision is conducted through a collaborative and distributed leadership model that strengthens coordination, shared responsibility, and teacher engagement. The process also adopts a reflective and developmental approach that encourages teacher openness, motivation, and professional growth. Overall, the study highlights that academic supervision functions not only as an evaluative mechanism but also as a continuous professional development system that enhances instructional quality and teacher effectiveness. These findings emphasize the importance of integrated instructional leadership in supporting sustainable school improvement at the primary education level.